Schiff Bases: A Captivating Scaffold with Potential Anticonvulsant Activity - Sahu, Rakesh; Shah, Kamal (Mini Reviews in Medicinal Chemistry, 2024)
One of the most important organic compounds, also known as a Schiff base, imine, or azomethine, has been associated with several biological processes. The group is a component of both natural or synthetic chemicals and functions as both a precursor and an intermediary in the synthesis of therapeutically active substances. The review highlights the various non-metal Schiff bases' structure-activity relationship (SAR) studies, general model, docking, and design approach for anticonvulsant actions. Schiff bases serve as linkers in numerous synthetic compounds with a variety of activities, according to the findings of several investigations. As a result, the current review will give readers a thorough understanding of the key ideas put forth by different researchers regarding the anticonvulsant properties of Schiff bases. It will serve as a valuable information source for those planning to synthesize new anticonvulsant molecules that contain Schiff bases as pharmacophores or biologically active moieties.
Keywords: structure-activity relationships (SAR)